2018
DOI: 10.1007/s10661-018-6632-4
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate analysis for source identification of pollution in sediment of Linggi River, Malaysia

Abstract: Rapid socioeconomic development in the Linggi River Basin has contributed to the significant increase of pollution discharge into the Linggi River and its adjacent coastal areas. The toxic element contents and distributions in the sediment samples collected along the Linggi River were determined using neutron activation analysis (NAA) and inductively coupled plasma-mass spectrometry (ICP-MS) techniques. The measured mean concentration of As, Cd, Pb, Sb, U, Th and Zn is relatively higher compared to the contine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 40 publications
0
8
2
Order By: Relevance
“…Potentially toxic elements (mg kg−1 ) in sediment samples of Wainivesi River, Tailevu, Fiji are characterized in terms of sediment quality guidelines (SQG) and are compared with those of previous literature studies.Garzanti et al, (2010); r Pattan et al, (2008); s Kim et al, (2010); t Jones and Jordan, (1979); u Elias et al, (2018); v Atibu et al, (2016).The average Cr concentration in sediment samples was noticed to be higher than LEL(Persuad et al, 1993), to be higher than the reported results for sediments in many countries in the worldZhang and Wang, 2001;Sorokina and Zarubina, 2011;Silva et al, 2016;Jones and Jordan, 1979;Elias et al, 2018;Atibu et al, 2016). The higher level of Ni was observed in the study area because of gold mining as well as Ni exist in gold bearing ore as pyrrhotite (Fe (1−x) S), which can contain up to 5% of Ni(Fashola et al, 2016).…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Potentially toxic elements (mg kg−1 ) in sediment samples of Wainivesi River, Tailevu, Fiji are characterized in terms of sediment quality guidelines (SQG) and are compared with those of previous literature studies.Garzanti et al, (2010); r Pattan et al, (2008); s Kim et al, (2010); t Jones and Jordan, (1979); u Elias et al, (2018); v Atibu et al, (2016).The average Cr concentration in sediment samples was noticed to be higher than LEL(Persuad et al, 1993), to be higher than the reported results for sediments in many countries in the worldZhang and Wang, 2001;Sorokina and Zarubina, 2011;Silva et al, 2016;Jones and Jordan, 1979;Elias et al, 2018;Atibu et al, 2016). The higher level of Ni was observed in the study area because of gold mining as well as Ni exist in gold bearing ore as pyrrhotite (Fe (1−x) S), which can contain up to 5% of Ni(Fashola et al, 2016).…”
mentioning
confidence: 87%
“…The average Pb concentration for this study was found to be higher than the Pb in surface soils (32 mg kg −1 ) worldwide average (Kabata-Pendias and Pendias, 2001) but was in line for Pb concentration (80 to 510 mg kg −1 ) in gold mine tailing(Ogola et la., 2002). The average Pb concentration was found to be greater than the river sediments in Bangladesh(Tamim et al, 2016), China(Zhang and Wang, 2001), Russia (Sorokina and Zarubina, 2011), Turkey (Pehlivan, 2010), Angola(Silva et al, 2016), Germany, Ireland (Jones and Jordan, (1979), Malaysia(Elias et al, 2018) and Congo(Atibu et al, 2016). This high Pb could be due the excessive use of gasoline additives, pesticides, as well as chemical fertilizers(Aboud and Nandini, 2009), sand extraction(Madzin et al, 2015) and mining activities(Emenike et al, 2020).…”
mentioning
confidence: 98%
“…Nonetheless, the average Cr concentration was below than the maximum acceptable Cr concentration in surface soil and the reported Cr level (486 mg kg −1 ) in gold mine tailing in Oman (Abdul-Wahab, S.; Marikar, 2012). Subsequently, the average Cr concentration in sediment samples was lower than the several rivers sediments reported in literature(Tamim et al., 2016; Khan et aldifferent river sediment in the world: Bangladesh (Tamim et al, 2016), China (Zhang and Wang, 2001), Russia (Sorokina and Zarubina, 2011), Turkey, Angola(Silva et al, 2016), Germany, Ireland (Jones and Jordan, (1979), Malaysia(Elias et al, 2018), Congo(Atibu et al, 2016). Therefore, it has been suggested that the sediments in the study area were free from Mn contamination with respect to the SQG threshold values.…”
mentioning
confidence: 79%
“…These can give adverse effects to the aquatic life [ 3 , 4 ]. Water, sediment and biota significantly play an important role in the assessment of the level of pollution, degree of contamination and toxicology effects [ [5] , [6] , [7] ].The major sources of inorganic pollution originated from anthropogenic sources are industrial, domestic, animal waste, mining, petroleum activities and agriculture activities, as well as industrial emissions [ 8 , 9 ].…”
Section: Methods Detailsmentioning
confidence: 99%
“…Each digestion batch was included at least two reagents blank acid, SRM (e.g., IAEA Soil-7) and duplicate samples. The microwave oven was programmed as follows: The power of the microwave setup at 1200 W, temperature setup for 200 °C, ramped for 20 min, held for 15 min, pressure setup at 0.6 MPa [ 7 ]. Sediment samples were digested for 20 min.…”
Section: Digestion Of Sediment Samplementioning
confidence: 99%